Physics-Based Modeling of Live Wildland Fuel Ignition Experiments in the Forced Ignition and Flame Spread Test Apparatus. Issue 9 (2nd September 2017) - Anand, C.; Shotorban, B.; Mahalingam, S.; McAllister, S.; Weise, D. R.
ABSTRACT: A computational study was performed to improve our understanding of the ignition of live fuel in the forced ignition and flame spread test apparatus, a setup where the impact of the heating mode is investigated by subjecting the fuel to forced convection and radiation. An improvement was first made in the physics-based model WFDS where the fuel is treated as fixed thermally thin elements and then it was utilized in this study. This improvement included bound water in addition to free water in fuel moisture content. The fuel was assumed to undergo evaporation of free and bound water, pyrolysis and char oxidation. Fuels with different moisture contents ranging from 0% to 130% were simulated under an identical heating condition. The simulated and the experimental ignition times compared reasonably well with each other. The time evolutions of simulated and experimental mass loss rates also compared well with each other. For all fuel moisture contents, it was observed that the release of bound moisture starts at temperatures greater than 200°C long after ignition time. This observation was consistent with the release of moisture observed at high temperatures in the experiments of live fuels.